Is this algebraic expression correct

  • #1
a(a-6) + 9 = 0
a2 - 6a + 9 = 0
(a - 3)(a - 3) = 0
a = -3

is this correct
 

Answers and Replies

  • #2
berkeman
Mentor
60,384
10,679
a(a-6) + 9 = 0
a2 - 6a + 9 = 0
(a - 3)(a - 3) = 0
a = -3

is this correct

All except for the last step. If a - 3 = 0, then a = ____
 

Related Threads on Is this algebraic expression correct

  • Last Post
Replies
9
Views
2K
  • Last Post
Replies
3
Views
2K
Replies
13
Views
684
  • Last Post
Replies
4
Views
2K
Replies
12
Views
3K
  • Last Post
Replies
5
Views
1K
  • Last Post
Replies
1
Views
2K
Replies
5
Views
2K
Replies
14
Views
4K
Replies
4
Views
13K
Top